2005
DOI: 10.1074/jbc.m410820200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of RalF, an ADP-ribosylation Factor Guanine Nucleotide Exchange Factor from Legionella pneumophila, Reveals the Presence of a Cap over the Active Site

Abstract: The Legionella pneumophila protein RalF is secreted into host cytosol via the Dot/Icm type IV transporter where it acts to recruit ADP-ribosylation factor (Arf) to pathogen-containing phagosomes in the establishment of a replicative organelle. The presence in RalF of the Sec7 domain, present in all Arf guanine nucleotide exchange factors, has suggested that recruitment of Arf is an early step in pathogenesis. We have determined the crystal structure of RalF and of the isolated Sec7 domain and found that RalF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 52 publications
4
97
0
3
Order By: Relevance
“…In the absence of chaperones, the prediction would be that these C-terminal translocation domains should be exposed and available for binding to components of the type IV secretion system. The RalF crystal structure has recently been solved (36), and, consistent with this prediction, these data show that the RalF C-terminal domain is located at the end of a long alpha helix comprised of amino acid residues 331-348 (Fig. 6, which is published as supporting information on the PNAS web site).…”
Section: Discussionsupporting
confidence: 58%
“…In the absence of chaperones, the prediction would be that these C-terminal translocation domains should be exposed and available for binding to components of the type IV secretion system. The RalF crystal structure has recently been solved (36), and, consistent with this prediction, these data show that the RalF C-terminal domain is located at the end of a long alpha helix comprised of amino acid residues 331-348 (Fig. 6, which is published as supporting information on the PNAS web site).…”
Section: Discussionsupporting
confidence: 58%
“…The C termini of both RalF and VirE2 are disordered and solvent exposed, as first indicated by secondary structure prediction algorithms and more recently by X-ray crystallography (5,88). These C-terminal domains (CTDs) are thus likely accessible to bind cognate T4SS receptors.…”
Section: C-terminal Secretion Signalsmentioning
confidence: 99%
“…The genomes of Legionella and of Rickettsia encode a type IV effector with a Sec7 domain homologous to that of eukaryotic ArfGEFs which functions as a GEF to activate host Arf GTPases. 65 The structure of Legionella RalF showed that the Sec7 domain is strongly autoinhibited by a C-terminal domain that blocks access to the Arf-binding site, 66 and a similar autoinhibited conformation was observed in the Rickettsia RalF homolog. 67 Both bacterial ArfGEFs are strongly activated by membranes, and the membrane-binding site is identical to the elements in the autoinhibitory domain that blocks the Arf-binding site.…”
Section: Regulation Of Bacterial Arfgefs By Membranesmentioning
confidence: 99%